An MPEG-2 decoder case study as a driver for a system level design methodology - van der Wolf, Pieter; Lieverse, Paul; Goel, Mudit; La Hei, David; Vissers, Kees (Hardware/Software Codesign 1999: Proceedings of the IEEE 7th International Conference, 1999)
We present a case study on the design of a heterogeneous architecture for MPEG-2 video decoding. The primary objective of the case study is the validation of the SPADE methodology for architecture exploration. The case study demonstrates that this methodology provides a structured approach to the efficient evaluation of the performance of candidate architectures for selected benchmark applications. We learned that the MPEG-2 decoder can conveniently be modeled as a Kahn process network using a simple API. Abstract models of architectures can be constructed efficiently using a library of generic building blocks. A trace driven simulation technique enables the use of these abstract models for performance analysis with correct handling of data dependent behavior. We performed a design space exploration to derive how the performance of the decoder depends on the busload and the frame rate.